The people and culture of Japan conversations between Donald Keene and Shiba Ryotaro - Shiba, Ryotaro 1923-1996; Keene, Donald; Gonzalez, Tony (Tokyo Japan Publishing Industry Foundation for Culture, 2016)
"The People and Culture of Japan features conversations between Donald Keene, a preeminent scholar of Japanese literature, and Shiba Ryotaro, the author who continued to contemplate the human condition through his original and distinctive lens of history. These talks-which mainly explore the foundations of Japanese culture-took place in Japanese on three occasions in 1971, in the historic cities of Nara, Kyoto, and Osaka. Drawing on their profound insights into Japan's relations with foreign cultures over the course of Japanese history, the two engage in a passionate discussion of their first-hand impressions and observations of Japanese culture." from back cover
The birth of Japanese culture -- Kukai, Ikkyu, and the University of Religion -- The world of gold, the world of silver: the aesthetics of troubled times -- The Japanese view of war -- Confucianism and Japanese morals -- Westerners in Japan -- Japanese morals, revisited -- The culture of Edo.
Includes index.
"This book is a complete translation of 'Nihonjin to nihonbunka' from 'The Collected Works of Donald Keene, Vol.9 ; Donarudo kiin chosakushu dai 9 kan: sekai no naka no nihonbunka (Shinchosa Publishing Co., Ltd., 2013), which is also in print since its original publication in 1972 as a book published by Chuokoron-Shinsha, Inc." -- title verso.
Foreword by Uemura Yoko.
Prefaces by Donald Keene and Shiba Ryotaro.
Text in English translated from the Japanese.
Keywords: Keene, Donald -- Interviews; Shiba, Ry?otar?o -- 1923-1996 -- Interviews; Shiba, Ry?otar?o -- 1923-1996 -- Interviews; Keene, Donald; Shiba, Ry?otar?o -- 1923-1996.; National characteristics, Japanese; Manners and customs; National characteristics, Japanese; Japan -- Social life and customs; Japan; Interviews